Booster COVID-19 vaccination against the SARS-CoV-2 Omicron variant: A systematic review - Yuxuan Du; Long Chen; Yuan Shi (Human Vaccines & Immunotherapeutics, 2022)
There is a wealth of data suggesting that the effectiveness of existing vaccines against the Omicron variant, the most mutated SARS-CoV-2 variant to date, has been substantially reduced if only primary vaccination is administered. Therefore, the effectiveness of booster vaccination against the Omicron variant has become a topic of current interest. We conducted a comprehensive search in PubMed, Embase, and the Cochrane Library to collect various pseudovirus neutralization tests or live virus neutralization tests for the Omicron variant, with serum specimens from booster vaccinees. We extracted neutralization titers for the Omicron variant, the original strain, and the other variants before and after booster vaccination, and then manually calculated the fold increase or decrease in neutralization titers for the Omicron variant relative to the other variants, and the fold increase in neutralization titers for the Omicron variant after booster vaccination compared with that before booster vaccination. In the two-dose vaccination regimen, the neutralization titers against the Omicron variant decreased substantially compared to the original strain and other variants. However, after booster vaccination, both homologous and heterologous booster vaccination, the neutralization of serum antibodies against the Omicron variant was significantly improved, although still lower than that of the original strain and other variants. The booster vaccination program based on existing vaccines can produce broad but incomplete immunity against the Omicron variant.